2007
DOI: 10.1002/pssb.200777112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states of ultrathin Co layers on Cu

Abstract: We studied ultrathin Co overlayers on top of vicinal Cu(100) and Cu(111) surface using high resolution photoemission spectroscopy to clarify the phenomena of surface alloying at low coverage. The valence band spectrum of Co/Cu(100) clearly shows the change in its electronic structure. A peak at the binding energy of 0.3 eV represents the mixing of Co and Cu at the surface, as has been reported by STM. This state becomes more enhanced upon annealing . Mixing the Co overlayer with Cu atoms on top of Cu (111) sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…Co and Cu have a very limited equilibrium miscibility at each end of the composition range at low temperatures (the miscibility of Cu in Co is 0.2% at 400 • C [1205]) [1206] and Cu surface segregation is limited in the range below 100 • C [838,[1207][1208][1209][1210] to 250 • C [1211][1212][1213]. Interface interdiffusion in submonolayer Co coverages has been identified in STM studies of Co/Cu(0 0 1) grown at room temperature [1214] and also confirmed in other reports [838,[1213][1214][1215][1216]. Above 2 ML, Co grows in an almost layer-by-layer mode at room temperature [528,529,1046,1211,1214,1217,1218]; below this thickness a layer-by-layer growth mode is observed at low deposition rates, ∼0.003 ML s −1 , while double layer growth is observed at higher rates, ∼0.3 ML s −1 [1214,1219], in agreement with the results of molecular dynamics simulations at 310 K which predict bilayer island formation at high deposition rates, attributed to an upward interlayer transport mechanism at the island edges [1220].…”
Section: Fcc Co/cu(0 0 1)supporting
confidence: 69%
“…Co and Cu have a very limited equilibrium miscibility at each end of the composition range at low temperatures (the miscibility of Cu in Co is 0.2% at 400 • C [1205]) [1206] and Cu surface segregation is limited in the range below 100 • C [838,[1207][1208][1209][1210] to 250 • C [1211][1212][1213]. Interface interdiffusion in submonolayer Co coverages has been identified in STM studies of Co/Cu(0 0 1) grown at room temperature [1214] and also confirmed in other reports [838,[1213][1214][1215][1216]. Above 2 ML, Co grows in an almost layer-by-layer mode at room temperature [528,529,1046,1211,1214,1217,1218]; below this thickness a layer-by-layer growth mode is observed at low deposition rates, ∼0.003 ML s −1 , while double layer growth is observed at higher rates, ∼0.3 ML s −1 [1214,1219], in agreement with the results of molecular dynamics simulations at 310 K which predict bilayer island formation at high deposition rates, attributed to an upward interlayer transport mechanism at the island edges [1220].…”
Section: Fcc Co/cu(0 0 1)supporting
confidence: 69%
“…Thus the Shockley surface state of Cu(111) is not much affected by the overlayer d-band of Fe. This shaded area can be the result of a step decoration where the polarization vector of the synchrotron light can be important in excitation of plasmons at the surface, with the existence of steps [20].…”
Section: Resultsmentioning
confidence: 99%